Self rectifying resistive memory device and method for manufacturing the same

KR103022820B1Active Publication Date: 2026-09-18PUSAN NAT UNIV IND UNIV COOPERATION FOUND
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020250054806
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2026-09-18
Estimated Expiration
2045-04-25

Smart Images

  • Figure 112025047536905-PAT00001_ABST
    Figure 112025047536905-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a resistive memory device comprising a two-dimensional perovskite and a ferroelectric in an active layer, wherein low voltage driving is possible due to the low activation energy of the two-dimensional perovskite, and at the same time, polarization of the ferroelectric is induced by the interaction between the ferroelectric and the two-dimensional perovskite, so that excellent self-rectification characteristics can be achieved without a separate diode.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a self-rectifying resistance memory and a method for manufacturing the same. Background Technology

[0002] With the recent proliferation of applications such as artificial intelligence, the Internet of Things, and high-performance computing, interest in next-generation non-volatile memory (NVM) technology capable of rapidly storing and reliably processing large amounts of data is growing. Among these, resistive memory devices, or memristors, which have the potential to alleviate the von Neumann bottleneck due to their simple cell structure, high power efficiency, and non-volatility characteristics, are attracting attention as a promising next-generation memory technology.

[0003] The above-mentioned resistive memory device generally has a crossbar array structure, which is a cross-array structure. Accordingly, it can store data in a high resistance state (HRS) and a low resistance state (LRS), and store information in each cell to read or erase data. However, since multiple cells are connected to a single electrode in this crossbar array structure, malfunctions such as random switching operations may occur due to a sneak current generated from adjacent memory cells. To solve this problem, a method using a 1S1R (1 Selector-1 Resistor) structure, which generally integrates a selector with the resistive memory cell one-to-one, has also been proposed. However, the addition of the selector has the disadvantage of potentially leading to increased process complexity, expanded cell area, and increased driving voltage.

[0004] Recently, 2D perovskite semiconductor materials capable of low-voltage operation have been attracting attention as a solution to improve these driving voltage issues. In particular, the 2D perovskite has the characteristic of being able to change the resistance state even with a small voltage because it has low activation energy. However, the 2D perovskite material has the disadvantage of being vulnerable to heat and moisture, and consequently, there is a problem of material degradation and performance deterioration when applied to high-temperature processes or to crossbar array structures and multilayer thin film structures where upper and lower electrodes intersect.

[0005] Therefore, there is a need to develop a novel resistive memory device capable of self-rectification while utilizing the low-voltage driving advantage of the above-mentioned two-dimensional perovskite, preventing the degradation of the perovskite occurring in the multilayer thin film structure. The problem to be solved

[0006] The present invention relates to a resistive memory device capable of self-rectification and a method for manufacturing the same. The purpose is to provide a resistive memory device in which the resistance state can be changed even at low voltage by means of a two-dimensional perovskite included in the active layer, and the self-rectification characteristics are improved by means of a ferroelectric material. means of solving the problem

[0007] To solve the above problems, the present invention provides a self-rectifying resistance memory device comprising a lower electrode, an upper electrode, and an active layer interposed between the lower electrode and the upper electrode, wherein the active layer comprises a channel penetrating the interior of the active layer and connecting the upper electrode and the lower electrode, and a ferroelectric material, wherein the channel comprises a two-dimensional perovskite, and the average diameter of the channel is 0.1 μm or more and 2 μm or less.

[0008] Based on a total of 100 parts by weight of the ferroelectric material, the content of the two-dimensional perovskite may be 10 parts by weight or more and 90 parts by weight or less.

[0009] The above ferroelectric material has a polarization value of 1 μC / cm 2 Above 10 μC / cm² 2 It may be less than or equal to

[0010] The above ferroelectric has a polarization value of 5 μC / cm 2 Above 7 μC / cm 2 It may be less than

[0011] The two-dimensional perovskite may be a compound represented by the following chemical formula 1.

[0012] [Chemical Formula 1]

[0013] Y2MX4

[0014] In the above chemical formula 1,

[0015] The above Y is butylammonium (BA), pentylammonium (PA), hexylammonium (HA), ammonium valeric acid (AVA), naphthylmethylammonium (NMA), phenylmethylammonium (PMA), or phenylethylammonium (PEA), and

[0016] The above M is Cu, Fe, Sn, Zn, Pb, Mn, Ge, Ni, Co, Cr, Pd, Cd, or Yb, and

[0017] The above X is F, Cl, Br, or I.

[0018] The above two-dimensional perovskite may comprise one or more selected from the group consisting of BA2PbI4, PEA₂PbI₄, and BA₂PbCl₄.

[0019] The above ferroelectric material may comprise a (co)polymer comprising one or more monomers selected from the group consisting of vinylidene fluoride, trifluoroethylene, chlorofluoroethylene, and chlorotrifluoroethylene.

[0020] The above ferroelectric material may comprise one or more selected from the group consisting of PVDF, P(VdF-TrFE), P(VdF-TrFE-CFE), and P(VdF-TrFE-CTFE).

[0021] The thickness of the active layer may be 0.1 μm or more and 1 μm or less.

[0022] The upper electrode may comprise one or more selected from the group consisting of Ag, Au, Al, Cu, Ni, Mg, Fe, Cr, Ti, Pt, Ru, Co, Mo, W, Li, Na, K, Cs, and Zn.

[0023] The lower electrode may comprise one or more selected from the group consisting of ITO, FTO, AZO, IZO, ZTO, and IZTO.

[0024] The present invention provides a method for manufacturing a self-rectifying resistance memory device comprising the steps of: preparing an active layer slurry comprising a two-dimensional perovskite, a ferroelectric material, and a solvent (S10); forming an active layer by coating the active layer slurry on one surface of a lower electrode (S20); and stacking an upper electrode on the other surface of the active layer that is not in contact with the lower electrode (S30), wherein the content of the two-dimensional perovskite is 10 parts by weight or more and 90 parts by weight or less based on a total weight of 100 parts by weight of the ferroelectric material in the active layer slurry.

[0025] The above (S20) step may involve coating the active layer slurry by a spin coating method. Effects of the invention

[0026] The self-rectifying resistance memory device according to the present invention includes a channel containing a two-dimensional perovskite and a ferroelectric material in the active layer, and thus has excellent self-rectifying characteristics and low-voltage driving characteristics, while the diameter size of the channel containing the two-dimensional perovskite is controlled so that the flow of current is smooth. Brief explanation of the drawing

[0027] FIG. 1 is a schematic diagram illustrating the shape of a part of the self-rectifying resistance memory device of the present invention as viewed from the side. FIG. 2 is a diagram illustrating the operation mechanism of the self-rectifying resistance memory device of the present invention. Specifically, when a positive voltage is applied to a resistance memory device in a high-resistance state, a SET operation occurs in which it switches to a low-resistance state (LRS), and in the LRS state, a conductive filament (Ag + It can be confirmed that a -doped CF) is formed. Additionally, it can be confirmed that a RESET operation occurs in which the conductive filament is ruptured (Rupture of CF) and transitions to a high resistance state (HRS) as a negative voltage is applied again. FIG. 3 is a schematic diagram illustrating one form of the self-rectifying resistance memory device of the present invention. Specifically, FIG. 3(a) is a perspective view of a resistance memory device, in which an active layer is stacked on one side of an ITO lower electrode and a plurality of Ag upper electrodes are stacked spaced apart from each other on the other side of the active layer. FIG. 3(b) is a side view of a part of the self-rectifying resistance memory device of FIG. 1. FIG. 3(c) is a diagram illustrating a state in which the polarity b-axis of the ferroelectric material is aligned horizontally due to intermolecular interaction between the two-dimensional perovskite and the ferroelectric material at the interface between the two-dimensional perovskite-containing channel and the ferroelectric material. FIG. 4 is a diagram briefly illustrating the manufacturing process of a self-rectifying resistance memory device of the present invention. First, the manufacturing process involves forming an active layer (P(VDF-TrFE)+BA2PbI4) by spin-coating an active layer slurry onto a lower electrode (Cleaned ITO glass). Subsequently, a self-rectifying resistance memory device is manufactured by stacking a plurality of upper electrodes (Ag electrodes) on the other side of the active layer using a thermal deposition process. FIG. 5 is an atomic force microscope (AFM) image of the active layer of the resistive memory device of Examples 1 to 4 and Comparative Example 1. Specifically, FIG. 5 (a) is an image of the active layer of Comparative Example 1, (b) is an image of Example 1, (c) is an image of Example 2, (d) is an image of Example 3, and (e) is an image of Example 4. FIG. 6 is an image of the active layer of the resistive memory device of Examples 1 to 4 and Comparative Example 1 taken with a field emission scanning electron microscope (FE-SEM). Specifically, FIG. 5 (a) is an image of the active layer of Comparative Example 1, (b) is an image of Example 1, (c) is an image of Example 2, (d) is an image of Example 3, and (e) is an image of Example 4. Figure 7 is a resistance switching IV curve showing the results of a DC voltage sweep experiment on the resistance memory device of Example 3. Figure 8 is a resistance switching IV curve showing the results of a DC voltage sweep experiment on the resistance memory device of Comparative Example 1. Figure 9 is a resistance switching IV curve showing the results of a DC voltage sweep experiment on the resistance memory device of Comparative Example 2. FIG. 10 is a graph showing the read current at +0.1V and -0.1V when an arbitrary voltage is applied in the low-resistance state of the resistance memory device of Example 3. The x-axis of the graph represents the applied voltage, the left y-axis represents the current read at +0.1V, and the right y-axis represents the current read at -0.1V. FIG. 11 is a resistance switching IV curve showing the results of a DC voltage sweep experiment to evaluate the stability of the resistance memory device of Example 3 over time and temperature. FIG. 11 (a) shows a single resistance switching IV curve obtained by performing a DC voltage sweep experiment on a daily basis after the resistance memory device was stored at room temperature and standby conditions for 32 days. FIG. 11 (b) shows a single resistance switching IV curve obtained by performing a DC voltage sweep experiment on the resistance memory device in a temperature range of 25 to 85°C. FIG. 12(a) shows the resistive memory element of Example 3, 10 4 This is a graph showing the current values ​​of the ON and OFF states over time at a reading voltage of +0.1V per second. FIG. 12 (b) is a graph showing the current values ​​of the ON and OFF states over time, measured and recorded by performing a total of 200 switching cycles on the resistor memory device of Example 3. Specific details for implementing the invention

[0028] Hereinafter, each component of the present invention is described in more detail so that a person skilled in the art to which the present invention pertains can easily implement it; however, this is merely an example, and the scope of the rights of the present invention is not limited by the following.

[0029] In this specification, the term “comprising” is used when listing materials, compositions, devices, and methods useful to the present invention, and is not limited to the examples listed.

[0030] In this specification, the terms “about” and “substantially” are used to mean a range of numerical or degree or an approximation thereof, taking into account inherent manufacturing and material tolerances, and are used to prevent an infringer from unfairly exploiting the disclosure in which precise or absolute figures provided to aid in understanding the invention are mentioned.

[0031] In this specification, when a component is described as being "on" one component, this means that, unless specifically stated otherwise, other components may be placed in between, without excluding the placement of other components.

[0032] In this specification, "2D perovskite" refers to a metal halide octahedron structural unit ([MX6] 4- It refers to a compound in which )(where M is a divalent metal cation and X is a halogen anion) are arranged in a planar manner to form an inorganic layer, and a monovalent organic cation is inserted between the inorganic layers to form a layered structure. For example, in the two-dimensional perovskite, butylammonium (BA) acts as the organic layer as the organic cation, and [PbI6] 4- It may be BA2PbI4, a compound in which the octahedron forms a two-dimensional planar structure.

[0033] In this specification, "average diameter of the channel" refers to a value obtained by measuring about 10 major axes of the channels observed by photographing the surface of the active layer with a field emission scanning electron microscope (FE-SEM) and then calculating the arithmetic mean.

[0035] The present invention will be described in more detail below.

[0037] The present invention provides a self-rectifying resistance memory device.

[0038] According to one embodiment of the present invention, the self-rectifying resistance memory device comprises a lower electrode, an upper electrode, and an active layer interposed between the lower electrode and the upper electrode, wherein the active layer comprises a channel penetrating the interior of the active layer and connecting the upper electrode and the lower electrode, and a ferroelectric material, wherein the channel comprises a two-dimensional perovskite, and the average diameter of the channel is 0.1 μm or more and 2 μm or less. Specifically, the active layer comprising the two-dimensional perovskite-containing channel and the ferroelectric material may be a single-layer active layer. Since the two-dimensional perovskite is susceptible to heat and moisture, if it is manufactured as a single-layer active layer that minimizes thin film, deposition, and etching processes, damage to the material can be minimized. Furthermore, the single-layer active layer has a simple structure, which may enable the implementation of a smaller cell size, and accordingly, an increase in integration density and memory capacity can be expected.

[0040] The above-described two-dimensional perovskite has the advantage of having a low activation energy, which is the energy barrier required for the movement of ions. Accordingly, the resistive memory device of the present invention, which is provided with a channel containing the above-described two-dimensional perovskite in the active layer, has the advantage of enabling resistance switching even at low voltage. Specifically, the channel penetrates the active layer and simultaneously contacts the upper electrode and the lower electrode, respectively, to enable the movement of ions and electrons. By including the above-described two-dimensional perovskite with low activation energy, the low-voltage driving characteristics of the self-rectifying resistive memory device can be improved. Furthermore, accordingly, the low-cost rectifying resistive memory device has the advantage of low overall power consumption and is advantageous for high-density memory applications.

[0042] Meanwhile, due to the strong intermolecular interaction between the ferroelectric material and the two-dimensional perovskite, self-alignment can be achieved in the ferroelectric material adjacent to the channel, and through this self-alignment, spontaneous polarization of the ferroelectric material can be formed at the interface between the two-dimensional perovskite-containing channel and the ferroelectric material. Therefore, as a result of the asymmetric formation of the electric field inside the active layer due to the high polarization of the ferroelectric material, the direction of movement of ions or electrons in the channel containing the two-dimensional perovskite can be controlled in a specific direction. That is, the self-rectifying resistance memory device comprising the ferroelectric material and the two-dimensional perovskite-containing channel in the active layer can exhibit excellent self-rectifying characteristics similar to those of a diode. As can be seen in Fig. 2 below, when a positive voltage is applied to the initial high resistance state (HRS) of the self-rectifying resistance memory device of the present invention (SET operation), metal ions (Ag) at the upper electrode + ) can be injected into the active layer and move to the lower electrode. At this time, in the low resistance state (LRS), metal ions can substitute lead vacancies in the two-dimensional perovskite to impart a doping effect, and as a result, conductive filaments through which holes can move are formed, allowing current to flow. Additionally, when a negative voltage is applied again (RESET operation), the metal ions are decomposed by the reverse electric field and return to the upper electrode, and as the conduction path disappears, it switches to a high resistance state where no current flows. In other words, in this way, the self-rectifying resistance memory device can perform resistance switching operation and self-rectification.

[0044] Specifically, the active layer may include a plurality of channels containing the two-dimensional perovskite, and more specifically, the plurality of channels may be dispersed within the active layer in the form of a dot pattern or a type of island. Accordingly, ions and electrons can move smoothly between the upper electrode and the lower electrode through the plurality of channels containing the two-dimensional perovskite within the active layer.

[0046] In addition, the average diameter of the channel may be 0.1 μm or more and 2 μm or less. Specifically, the average diameter of the channel may refer to the horizontal length of the BA2PbI4 channel shown in Fig. 1 below. Specifically, the diameter of the channel may be 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 0.7 μm or more, 0.9 μm or more, or 1 μm or more, and may also be 2 μm or less, 1.5 μm or less, or 1 μm or less. When the diameter of the channel satisfies the above range, ions and electrons can move smoothly through a sufficiently wide channel, and accordingly, the low-voltage driving performance of the self-rectifying resistance memory device may be excellent. If the diameter of the channel is smaller than the above range, current may not flow smoothly through the channel. In addition, if the diameter of the channel exceeds the above range, the relative content and volume of the ferroelectric material decrease, and the rectification action by the ferroelectric material may not occur smoothly.

[0048] In addition, specifically, the self-rectifying resistance memory device may have a shape in which a single layer of active layer is provided on one side of a single lower electrode, and a plurality of upper electrodes are distributed spaced apart from each other. For example, as shown in FIG. 3(a) below, the self-rectifying resistance memory device may have a shape in which an active layer is provided on an ITO-coated glass substrate, and a plurality of Ag upper electrodes are distributed spaced apart from each other on the other side of the active layer.

[0050] In summary, by means of the channel including the two-dimensional perovskite and the ferroelectric material, the active layer can change its resistance state at low voltage while preventing leakage current without a selector, and the electric field inside the active layer is formed asymmetrically by the polarization of the ferroelectric material, so excellent self-rectification characteristics can be achieved. In addition, current can effectively move through the active layer by means of the channel having a diameter of 0.1 to 2 μm.

[0052] According to one embodiment of the present invention, the content of the two-dimensional perovskite based on 100 parts by weight of the total ferroelectric material may be 10 parts by weight or more and 90 parts by weight or less. Specifically, based on 100 parts by weight of the total weight of the ferroelectric material, the content of the two-dimensional perovskite may be 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more, and may also be 90 parts by weight or less, 80 parts by weight or less, 70 parts by weight or less, 60 parts by weight or less, 50 parts by weight or less, or 40 parts by weight or less. When the content ratio of the two-dimensional perovskite and the ferroelectric material in the active layer satisfies the above range, a channel containing the two-dimensional perovskite in the active layer is sufficiently formed so that current can flow smoothly, and at the same time, the ferroelectric material is also sufficiently present so that the self-rectification characteristics of the resistive memory device due to the polarization of the ferroelectric material may also be excellent.

[0054] According to one embodiment of the present invention, the ferroelectric material has a polarization value of 1 μC / cm 2 Above 10 μC / cm² 2 It may be less than or equal to. Specifically, the ferroelectric material has a polarization value of 1 μC / cm 2 Above, 2 μC / cm² 2 Above, 3 μC / cm² 2 Above, 4 μC / cm² 2 Above, or 5 μC / cm² 2 It may be abnormal, and also, 10 μC / cm 2 ≤ 9 μC / cm² 2 ≤ 8 μC / cm² 2 Less than or equal to 7 μC / cm² 2 It may be less than or equal to. Preferably, the polarization value of the ferroelectric is 5 μC / cm 2 Above 7 μC / cm 2 The range may be as follows. The polarization value of the ferroelectric material was measured by polarization-voltage characteristic analysis of a ferroelectric thin-film capacitor manufactured by the same process in a composition without perovskite. When the polarization value of the ferroelectric material satisfies the above range, an asymmetric charge distribution in the active layer can be induced more effectively, and consequently, the self-rectification characteristics of the resistive memory device may be excellent. Furthermore, when the polarization value satisfies the above range, effects such as an increase in the self-rectification ratio, resistance state retention, and improved switching cycle characteristics can be achieved.

[0056] According to one embodiment of the present invention, the two-dimensional perovskite may be a compound represented by the following chemical formula 1.

[0057] [Chemical Formula 1]

[0058] Y2MX4

[0059] In the above chemical formula 1, Y is butylammonium (BA), pentylammonium (PA), hexylammonium (HA), ammonium valeric acid (AVA), naphthylmethylammonium (NMA), phenylmethylammonium (PMA) or phenylethylammonium (PEA), M is Cu, Fe, Sn, Zn, Pb, Mn, Ge, Ni, Co, Cr, Pd, Cd or Yb, and X is F, Cl, Br or I. When a compound of the above chemical formula 1 is used as a two-dimensional perovskite, low-voltage operation of a resistive memory device may be possible through the low activation energy of the two-dimensional perovskite, and self-rectification characteristics may be further improved through intermolecular interactions with the ferroelectric material.

[0061] According to one embodiment of the present invention, the two-dimensional perovskite may comprise one or more selected from the group consisting of BA2PbI4, PEA₂PbI4, and BA₂PbCl₄. Specifically, the two-dimensional perovskite may be BA2PbI4. When the compound listed above, specifically BA2PbI4, is used as the two-dimensional perovskite, the generation of leakage current can be minimized due to the high insulating properties of BA2PbI4, and accordingly, the formation of conductive filaments by ion implantation can be precisely controlled, thereby enabling stable ON / OFF switching of the resistive memory device. In addition, low-voltage operation of the resistive memory device may be possible due to the low activation energy of BA2PbI4.

[0063] According to one embodiment of the present invention, the ferroelectric material may comprise a (co)polymer comprising one or more monomers selected from the group consisting of vinylidene fluoride, trifluoroethylene, chlorofluoroethylene, and chlorotrifluoroethylene. When the ferroelectric material is a polymer or copolymer comprising at least one of the monomers described above, internal polarization of the ferroelectric material is induced more effectively by the high dielectric constant, and accordingly, the self-rectification characteristics of the resistive memory device may be excellent. Furthermore, in the case of the copolymer, the degrees of freedom of the polymer chain can be controlled by adjusting the content of heterogeneous monomers within the copolymer, and accordingly, the self-rectifying resistive memory device may be suitable for application in flexible devices or bio-implantable devices.

[0065] According to one embodiment of the present invention, the ferroelectric material may comprise one or more selected from the group consisting of PVdF, P(VdF-TrFE), P(VdF-TrFE-CFE), and P(VdF-TrFE-CTFE). Specifically, the ferroelectric material may be a copolymer of vinylidene fluoride and trifluoroethylene (P(VdF-TrFE)). Since the polymer or copolymer enables the switching of polarization states even at low voltages by a low forced field, it may exhibit excellent self-rectification characteristics. Furthermore, when the active layer comprises the polymer or copolymer as the ferroelectric material, stable switching may be possible even at low voltages. Moreover, since P(VdF-TrFE) is capable of solution processing and possesses high mechanical flexibility, it may be easy to fabricate flexible devices.

[0067] According to one embodiment of the present invention, the thickness of the active layer may be 0.1 μm or more and 1 μm or less. Specifically, the thickness of the active layer may be 0.1 μm or more, 0.2 μm or more, or 0.3 μm or more, and may also be 1 μm or less, 0.75 μm or less, or 0.5 μm or less. When the thickness of the active layer satisfies the above range, ions and electrons can move smoothly through the active layer, while preventing leakage current from occurring in the active layer film due to the thickness of the active layer being excessively thin. In addition, both self-rectification characteristics and low-voltage driving characteristics may be excellent within the above thickness range.

[0069] According to one embodiment of the present invention, the upper electrode may comprise one or more selected from the group consisting of Ag, Au, Al, Cu, Ni, Mg, Fe, Cr, Ti, Pt, Ru, Co, Mo, W, Li, Na, K, Cs, and Zn. Specifically, the upper electrode may comprise Ag. The upper electrode is a highly conductive metal substrate comprising the metal element, which may have excellent compatibility with organic materials as it is capable of thermal deposition at a low temperature, and may be positioned on the aforementioned active layer to transfer metal cations to the lower electrode through the active layer.

[0071] According to one embodiment of the present invention, the lower electrode may comprise one or more selected from the group consisting of ITO (indium tin oxide), FTO (fluorine tin oxide), AZO (aluminum zinc oxide), IZO (indium zinc oxide), ZTO (zinc tin oxide), and IZTO (indium zinc tin oxide). Specifically, the lower electrode may be an electrode coated with an oxide such as ITO on a glass substrate. The lower electrode is a highly conductive substrate containing the oxide, which can stably maintain the flow of current, and the oxide can be formed as a thin film on the glass substrate, which may be advantageous for miniaturizing the entire self-rectifying resistance memory device.

[0073] The present invention provides a method for manufacturing a self-rectifying resistance memory device.

[0074] The method for manufacturing the above-described self-rectifying resistance memory device may be a method for manufacturing the above-described self-rectifying resistance memory device, and below, parts that overlap with the content regarding the self-rectifying resistance memory device described above will be omitted.

[0076] According to one embodiment of the present invention, the method for manufacturing the self-rectifying resistance memory device comprises the steps of: preparing an active layer slurry comprising a two-dimensional perovskite, a ferroelectric material, and a solvent (S10); forming an active layer by coating the active layer slurry on one surface of a lower electrode (S20); and stacking an upper electrode on the other surface of the active layer that is not in contact with the lower electrode (S30). The content of the two-dimensional perovskite may be 10 parts by weight or more and 90 parts by weight or less based on 100 parts by weight of the total weight of the ferroelectric material in the active layer slurry. By forming an active layer on a lower electrode using the two-dimensional perovskite and the ferroelectric material, the method for manufacturing the self-rectifying resistance memory device can manufacture a self-rectifying resistance memory device with excellent self-rectifying characteristics and low-voltage driving characteristics.

[0078] The above step (S10) may be a step of preparing an active layer slurry by adding a two-dimensional perovskite and a ferroelectric to the solvent. Specifically, the solvent may be an organic solvent such as dimethylformamide, and the above step (S10) may be a step of introducing the two-dimensional perovskite and the ferroelectric to an organic solvent at a temperature of 60 to 80°C and stirring so that the two-dimensional perovskite and the ferroelectric are evenly dispersed within the active layer slurry.

[0080] At this time, the content of the two-dimensional perovskite based on 100 parts by weight of the total weight of the ferroelectric material in the active layer slurry may be 10 parts by weight or more and 90 parts by weight or less. Specifically, based on 100 parts by weight of the total weight of the ferroelectric material in the active layer slurry, the content of the two-dimensional perovskite may be 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more, and may also be 90 parts by weight or less, 70 parts by weight or less, or 50 parts by weight or less. When the content ratio of the two-dimensional perovskite and the ferroelectric material in the active layer slurry satisfies the above range, a channel containing the two-dimensional perovskite in the active layer can be sufficiently formed, and accordingly, the diameter of the channel containing the two-dimensional perovskite can satisfy a range of 0.1 μm or more and 2 μm or less.

[0082] The above step (S20) may be a step of forming an active layer by applying the active layer slurry to one surface of the lower electrode and drying it. Specifically, the above step (S20) may be a step of forming an active layer having a thickness of 0.1 μm or more and 1 μm or less by applying the active layer slurry and drying it at a temperature of 50°C or more and 100°C or less to remove residual solvent.

[0084] The above step (S30) may be a step of laminating an upper electrode on the other side of the active layer that is not in contact with the lower electrode. Specifically, in the above step (S30), when laminating the upper electrode, the upper electrode and the active layer are bonded using a thermal deposition process, thereby minimizing potential damage at the interface between the active layer and the upper electrode.

[0086] According to one embodiment of the present invention, step (S20) may involve coating the active layer slurry by a spin coating method. Step (S20) may involve forming an active layer by spin coating the active layer slurry at a speed of 1,000 rpm or more and 1,500 rpm or less for a time of 30 seconds or more and 2 minutes or less. When spin coating is used as a method for coating the active layer slurry, the β phase of the ferroelectric material can be easily formed, and accordingly, strong polarization of the active layer is induced, resulting in excellent self-rectification characteristics. Furthermore, spin coating has the advantage of being simple and rapid, offering excellent reproducibility, as well as enabling the formation of an active layer of a thin film.

[0088] Hereinafter, the present invention will be described in detail with reference to examples to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention is not to be interpreted as being limited to the embodiments described below. The embodiments of this specification are provided to more completely explain the present invention to those with average knowledge in the art.

[0090] Examples and Comparative Examples

[0091] Manufacturing of resistive memory devices

[0092] <Example 1>

[0093] P(VdF-TrFE) (a molar ratio of vinylidene fluoride monomer to trifluoroethylene monomer of 7:3) was prepared as a ferroelectric material and BA2PbI4 as a secondary perovskite, and each was added to dimethylformamide in a weight ratio of 1:0.23 to prepare an active layer slurry by vigorously stirring at a temperature of 70°C. Meanwhile, a glass substrate coated with ITO was prepared as the bottom electrode, and after sequentially washing with acetone and 2-propanol, UV-O3 treatment was performed for 15 minutes for each washing step. Subsequently, the active layer slurry was applied to one surface of the bottom electrode by spin coating at a speed of 1,500 rpm for 60 seconds, and then dried at a temperature of 70°C for 60 minutes to remove residual solvent. The thickness of the formed active layer was approximately 350 nm, and multiple channels containing the secondary perovskite were evenly distributed on the surface of the active layer, with the diameter of each channel being approximately 415 nm. Subsequently, a 100 nm thick Ag substrate was prepared as the top electrode and a self-rectifying resistive memory device was fabricated by depositing it on the other side of the active layer using thermal deposition with a shadow mask. At this time, the area of ​​the resistive memory device was approximately 380 μm² 2 It was.

[0094] Meanwhile, regarding the above P(VdF-TrFE), the ferroelectric thin-film capacitor manufactured using the same process as the active layer fabrication in a composition not containing the secondary perovskite was measured using the polarization-voltage characteristic analysis method, and the result was 6 μC / cm 2 The polarization value of was obtained.

[0095] <Example 2>

[0096] In the above Example 1, a self-rectifying resistance memory device was manufactured in the same manner as in Example 1, except that the active layer slurry was prepared using P(VdF-TrFE) and BA2PbI4 in a weight ratio of 1:0.3.

[0097] <Example 3>

[0098] In the above Example 1, a self-rectifying resistance memory device was manufactured in the same manner as in Example 1, except that the active layer slurry was prepared using P(VdF-TrFE) and BA2PbI4 in a weight ratio of 1:0.37.

[0099] <Example 4>

[0100] In the above Example 1, a self-rectifying resistance memory device was manufactured in the same manner as in Example 1, except that the active layer slurry was prepared using P(VdF-TrFE) and BA2PbI4 in a weight ratio of 1:0.43.

[0101] <Comparative Example 1>

[0102] In the above Example 1, a resistive memory device was manufactured in the same manner as in Example 1, except that the active layer slurry was prepared without using the above BA2PbI4.

[0103] <Comparative Example 2>

[0104] In the above Example 1, a resistive memory device was manufactured in the same manner as in Example 1, except that the active layer slurry was prepared without using the above P(VdF-TrFE).

[0106] Experimental Example

[0107] Experimental Example 1. Analysis of surface morphology of the active layer according to 2D perovskite content

[0108] The surface morphology of the active layer of the above examples and comparative examples was analyzed using an atomic force microscope (AFM) and a field emission scanning electron microscope (FE-SEM), respectively.

[0109] First, the active layers of the above examples and comparative examples were measured using a non-contact mode AFM (NX10, Park Systems) to observe the distribution of channels containing two-dimensional perovskites as shown in Fig. 5 below. As shown in Fig. 5 below, no channels were observed in the active layer of Comparative Example 1, which did not use two-dimensional perovskites. On the other hand, in the active layers of Examples 1 to 4, which used BA2PbI4 as the two-dimensional perovskite, it was confirmed that channels containing two-dimensional perovskites were distributed in an island form, and it was confirmed that as the content of the two-dimensional perovskite increased, the number and diameter of the channels increased.

[0110] The fact that the diameter of the above channel increases as the content of the two-dimensional perovskite increases can be confirmed in more detail from images taken with an FE-SEM (GEMINI500, Carl ZEIS). As shown in Fig. 6 below, channels cannot be observed in the active layer of Comparative Example 1, which does not use two-dimensional perovskite, but in the active layers of Examples 1 to 4, it can be confirmed that channels containing two-dimensional perovskite are formed with a diameter of 400 nm to 1 μm. Specifically, it can be confirmed that the diameter of the channel increases to the level of 1 μm as the content of the two-dimensional perovskite increases.

[0112] Experimental Example 2. Evaluation of Resistance Switch Operation and Self-Rectification Characteristics of a Resistive Memory Device

[0113] The resistance switching operation and self-rectification characteristics were evaluated for the self-rectifying resistive memory device of Example 3 and the resistive memory devices of Comparative Examples 1 and 2. Specifically, the characteristics were measured by applying a voltage to the upper electrode of the resistive memory devices of the examples and comparative examples and under a DC voltage sweep (+0.4 V to -0.4 V). As can be seen in the IV curve of Fig. 7 below, when sweeping a positive (+) voltage from 0 V to +0.4 V, at +0.32 V, approximately 10-5 A (or 15.5 A / m 2 A rapid resistance switching occurred along with the ON current, transitioning to the low resistance state (LRS) (set operation). Subsequently, when performing a reverse sweep from +0.4 V to -0.4 V, approximately 10 from 0 V -11 A (or 3.6X10 -5 A / m 2 It switched to the High Resistance State (HRS) with an OFF current below ) (reset operation). As a result, when read at +0.1 V, approximately 10 6 The LRS / HRS (ON / OFF) current ratio was shown. From the experimental results above, it can be confirmed that the self-rectifying resistor memory device of the present invention can smoothly perform resistance switching operation even at low voltage (set voltage is approximately 0.32 V). Furthermore, the self-rectifying resistor memory device of the present invention exhibits a diode-shaped IV curve in which the current increases rapidly at positive voltage, whereas the current is extremely suppressed at negative voltage, confirming that it has excellent self-rectifying characteristics.

[0114] In addition, as can be seen in Fig. 10 below, the rectified state of the low-resistance state of the self-rectifying resistance memory device of Example 3 was maintained as long as the externally applied voltage did not drop below -0.15 V, and when it fell below -0.15 V, it switched from the low-resistance state to the high-resistance state, from which it can be confirmed that the reset voltage is -0.15 V.

[0116] Meanwhile, as can be seen in Fig. 8 below, the resistive memory device of Comparative Example 1, which does not contain a two-dimensional perovskite, has a left-right symmetrical IV curve and shows almost no current flow. In other words, it exhibited only the characteristics of a low-conductivity insulator without any rectification or switching phenomena, and it can be confirmed that low-voltage driving is also impossible. Furthermore, as can be seen in Fig. 9 below, the resistive memory device of Comparative Example 2, which does not contain a ferroelectric material, is unable to self-rectify, so the IV curve appears almost bipolar, and it can be confirmed that current flows at both positive and negative voltages, causing unstable switching regardless of the current direction.

[0118] Experimental Example 3. Evaluation of the stability of a self-rectifying resistance memory device over time

[0119] In order to evaluate the stability of the self-rectifying resistance memory device, the self-rectifying resistance memory device of Example 3 was stored for a long period under room temperature and ambient conditions, and then the resistance switch operation by date was tested in the same manner as in Experimental Example 2.

[0120] As shown in the IV curve of Fig. 11(a) below, it can be confirmed that the self-rectifying resistance memory device maintains similar hysteresis from day 1 to day 32 under room temperature and ambient conditions. Specifically, since the current difference between LRS and HRS is maintained to a similar degree, and the characteristics of non-volatile memory are maintained, it can be seen that the self-rectifying resistance memory device has excellent ambient stability even in ambient conditions.

[0122] Experimental Example 4. Evaluation of the stability of a self-rectifying resistance memory device at high temperatures

[0123] In order to evaluate the stability of the self-rectifying resistance memory device, the temperature of the self-rectifying resistance memory device of Example 3 was raised from room temperature (25°C) to high temperature (85°C), and the resistance switch operation by date was tested in the same manner as in Experimental Example 2.

[0124] As shown in the IV curve of Fig. 11(b) below, it can be confirmed that the self-rectifying resistance memory device of Example 3 maintains hysteresis similar to that at room temperature even at high temperatures. In addition, since the switching voltage and LRS current do not appear significantly even at high temperatures, it can be confirmed that the thermal stability of the self-rectifying resistance memory device is excellent.

[0126] Experimental Example 5. Evaluation of Data Retention and Durability of Self-Regulating Resistance Memory Device

[0127] Data retention and endurance over time were evaluated for the self-rectifying resistance memory device of Example 3 above.

[0129] First, the self-rectifying resistor memory element of Example 3 is set to the ON state (LRS) and OFF state (HRS), respectively, by sweeping the voltage in the range of -0.4 V to +0.4 V, and then each state is set to 10 under a read voltage of +0.1 V. 4 Monitored for more than 2 seconds. As shown in Fig. 12(a) below, the respective current values ​​in both the ON state (LRS) and OFF state (HRS) are 10 4 It was maintained stably for more than a second, and accordingly, it can be confirmed that the self-rectifying resistance memory device of the present invention exhibits excellent data preservation characteristics. In particular, it can be confirmed that a high current level was continuously maintained in the ON state, and that current leakage was significantly suppressed even in the OFF state.

[0131] Next, a switching endurance evaluation was performed on the self-rectifying resistor memory device of Example 3 to verify whether it is possible to repeatedly switch between the ON state (LRS) and the OFF state (HRS). Specifically, the ON state was set by a voltage sweep up to -0.4 V, and the OFF state was set by a voltage sweep up to +0.4 V. Each state was measured under a read voltage of +0.1 V, and the current value was monitored over a total of 200 switching cycles.

[0132] As can be seen in Fig. 12(b) below, the ON and OFF states were stably maintained even after undergoing repetitive switching cycles, and it was confirmed that the difference in current between the two states was clearly maintained. From this, it was confirmed that the self-rectifying resistance memory device of the present invention has good repeatability and high reproducibility.

[0134] Experimental Example 6. Performance comparison with conventional self-rectifying resistance memory device

[0135] The switching voltage, rectification ratio, etc. of the self-rectifying resistance memory device of Example 3 above and a conventional self-rectifying resistance memory device were compared and are shown in Table 1 below. For the conventional self-rectifying resistance memory devices, the active layer configuration used was a metal oxide-single layer (Comparative Example a), a metal oxide-double layer (Comparative Example b), a metal oxide-triple layer (Comparative Example c), a silicon compound (Comparative Example d), an organic compound (Comparative Example e), a ferroelectric (Comparative Example f), and a ferroelectric and semiconductor heterojunction (Comparative Examples g, h).

[0137] division Rectification method Switching ratio (I ON / I OFF @V READ ) rectification ratio V SET / V RESET [V / V] Data retention time[s] Repetitive operation lifespan [cycle] Example 3 (Ag / P(VDF-TrFE):BA2PbI4 / ITO) Self-polarization 10 6 @+0.1V 10 6 +0.3 / -0.4 >10 4 100 (DC) Comparative example a(Pt / TaO x / n-Si) Schottky barrier 10 4 @+0.8V 2.4X10 2 -4 / +1.5 2X10 3 100 (DC) Comparative example b (Pt / Ta2O5 / HfO2 / TiN) Schottky barrier 10 3 @+7V 10 4 +12 / -8 >10 6 100 (DC) Comparative Example c (Pt / Ta2O5 / HfO 2-x / TiO x / Ti) Schottky barrier 10 6 @+2.5V 10 6 +8 / -4 >10 4 N / A Comparative Example d(p-Si / SiO2 / n-Si) PiN junction 10 4 @+2V 10 5 +7.5 / +4.5 >10 5 100 (DC) Comparative example e (Ag / FJU-23-H2O a) / Ag) Asymmetric molecular structure 10 5 @+0.05V 10 5 +0.2 / -0.5 >10 4 100 (DC) Comparative example f(Au / BaTiO3 / Nb:SrTiO3) Asymmetric potential barrier 10 3 @+0.5V 10 3 +3 / -3 N / A 200 (Pulse) Comparative Example g(Al / LiF / P(VDF-TrFE):P3HT b) / Ag) Schottky barrier 10 2 @+3V 10 3 +20 / -20 >10 5 10 3 (Pulse) Comparative example h(Al / P(VDF-TrFE):ZnO / Pt) Schottky barrier 10 2 @+3V 10 4 +20 / -20 10 4 10 7 (Pulse)

[0139] (a) above is a Metal organic framework {[ZnL(H2O)]3(H2O)4} n , b) is Poly(vinylidene fluoride-co-trifluoroethylene): poly(3-hexylthiophene-2,5-diyl))

Claims

Claim 1 A self-rectifying resistance memory device comprising: a lower electrode; an upper electrode; and an active layer interposed between the lower electrode and the upper electrode, wherein the active layer comprises a channel penetrating the interior of the active layer and connecting the upper electrode and the lower electrode, and a ferroelectric material, wherein the channel comprises a two-dimensional perovskite, the average diameter of the channel is 0.1 μm or more and 2 μm or less, and the content of the two-dimensional perovskite is 10 parts by weight or more and 70 parts by weight or less based on a total of 100 parts by weight of the ferroelectric material. Claim 2 delete Claim 3 In claim 1, the ferroelectric material has a polarization value of 1 μC / cm 2 Above 10 μC / cm² 2 A self-rectifying resistance memory device that is less than or equal to the following. Claim 4 In claim 1, the ferroelectric material has a polarization value of 5 μC / cm 2 Above 7 μC / cm 2 A self-rectifying resistance memory device that is less than or equal to the following. Claim 5 A self-rectifying resistance memory device according to claim 1, wherein the two-dimensional perovskite is a compound represented by the following chemical formula 1: [Chemical Formula 1] Y2MX4. In the above chemical formula 1, Y is butylammonium (BA), pentylammonium (PA), hexylammonium (HA), ammonium valeric acid (AVA), naphthylmethylammonium (NMA), phenylmethylammonium (PMA), or phenylethylammonium (PEA), M is Cu, Fe, Sn, Zn, Pb, Mn, Ge, Ni, Co, Cr, Pd, Cd, or Yb, and X is F, Cl, Br, or I. Claim 6 A self-rectifying resistance memory device according to claim 1, wherein the two-dimensional perovskite comprises one or more selected from the group consisting of BA2PbI4, PEA2PbI4, and BA2PbCl₄. Claim 7 A self-rectifying resistance memory device according to claim 1, wherein the ferroelectric material comprises a (co)polymer comprising one or more monomers selected from the group consisting of vinylidene fluoride, trifluoroethylene, chlorofluoroethylene, and chlorotrifluoroethylene. Claim 8 A self-rectifying resistance memory device according to claim 1, wherein the ferroelectric material comprises one or more selected from the group consisting of PVDF, P(VdF-TrFE), P(VdF-TrFE-CFE), and P(VdF-TrFE-CTFE). Claim 9 A self-rectifying resistance memory device according to claim 1, wherein the thickness of the active layer is 0.1 μm or more and 1 μm or less. Claim 10 A self-rectifying resistance memory device according to claim 1, wherein the upper electrode comprises one or more selected from the group consisting of Ag, Au, Al, Cu, Ni, Mg, Fe, Cr, Ti, Pt, Ru, Co, Mo, W, Li, Na, K, Cs and Zn. Claim 11 A self-rectifying resistance memory device according to claim 1, wherein the lower electrode comprises one or more selected from the group consisting of ITO, FTO, AZO, IZO, ZTO, and IZTO. Claim 12 A method for manufacturing a self-rectifying resistance memory device comprising: a step (S10) of preparing an active layer slurry comprising a two-dimensional perovskite, a ferroelectric material, and a solvent; a step (S20) of forming an active layer by coating the active layer slurry on one surface of a lower electrode; and a step (S30) of stacking an upper electrode on the other surface of the active layer that is not in contact with the lower electrode, wherein the content of the two-dimensional perovskite is 10 parts by weight or more and 70 parts by weight or less based on a total weight of 100 parts by weight of the ferroelectric material in the active layer slurry. Claim 13 A method for manufacturing a self-rectifying resistance memory device, wherein the above step (S20) is to coat the active layer slurry by a spin coating method.

Citation Information

Patent Citations

  • Resistance change memory device including organic-inorganic hybrid perovskite as resistance change layer and method for fabricating the same

    KR1020170049758A

  • Electronic Synaptic Device and Method for Manufacturing Same

    KR1020220040213A

  • Electronic device

    KR1020230062062A

  • Resistance switching memory device using quantum dots and manufacturing method thereof

    KR1020230079957A